Phylogeny of selected species of subgenus Culex mosquitoes (Diptera: Culicidae) from the U.S., Puerto Rico, and Guatemala, based on nucleotide sequences from three genes - Deus, Stephen, author; Black, William C., IV, advisor (Colorado State University. Libraries, 2009)
Phylogeny was inferred for subgenus Culex mosquitoes from the United States, Guatemala and Puerto Rico based on aligned nucleotide sequences from three genetic regions: 705 base pairs (bp) of the mitochondrial cytochrome oxidase subunit II (COII) gene, a region of ribosomal DNA containing internal transcribed spacers (ITS) 1 and 2, and 850 bp of the nuclear protein-coding white gene. Each gene was evaluated for its utility in phylogenetic inference, as were four methods of phylogenetic analysis: neighbor-joining distance, parsimony, maximum likelihood, and Bayesian analysis. A simultaneous analysis of the COII and ITS data was performed using the Bayesian method. The phylogeny challenges the monophyly of subgenus Culex and helps clarify the phylogenetic positions of subgenus Phenacomyia and genus Deinocerites relative to subgenus Culex.
Keywords: Culex; mosquitoes; nucleotide sequences; entomology; evolution and development; evolution and development